FATOR YANG MEMPEGARUHI KINERJA PEGAWAI SATUAN POLISI PAMONG PRAJA KABUPATEN ROKAN HULU - Hasibuan, CANDRA SAPUTRA (Jurnal Mahasiswa Prodi SI Manajemen, 2013)
In realizing good governance ( Good Governance) at the same time as guidance in applying governmental management which orient [at] performance. Rokan Pate;Upstream have Vision that is “ realizing Rokan Pate;Upstream as best sub-province [in] province of Riau year 2016. Satpol PP have duty assist government to create a[n orderly area condition, tentram and regular so that management of governmental wheel can go well. This research to know how far performance Officer Of Satpol PP Rokan Pate;Upstream. This Research use descriptive research type, population in this research [of] officer of Satpol PP sub-province of Rokan Pate;Upstream counted 296 people, hence the him of 170 people , by using technique of simple sampling random. Pursuant to research got that factor influencing performance Officer Of Satpol PP Rokan Pate;Upstream is Motivation with value 0.127 > 0.05, and environmental with value 0.078 > 0,05, while Environmental - 0,156 < 0,05. Pursuant to research result that Factor Motivate and Ability influence performance Officer Of Office of Satpol PP Rokan Pate;Upstream, while Environment [do] not influence performance of Satpol PP Sub-Province of Rokan Pate;Upstream